Clonorchis sinensis on the prognosis of patients with spontaneous rupture of Hepatocellular Carcinoma: An inverse probability of treatment weighting analysis. - Hang-Hang Ni; Zhan Lu; Cheng-Lei Yang; Yu-Ting Lv; Chun-Xiu Lu; Bang-De Xiang (Public Library of Science (PLoS), 2024)
Background We examined the impact of the Clonorchis sinensis (C. sinensis) infection on the survival outcomes of spontaneous rupture Hepatocellular Carcinoma (srHCC) patients undergoing hepatectomy. Methods Between May 2013 and December 2021, 157 consecutive srHCC patients who underwent hepatectomy were divided into an no C. sinensis group (n = 126) and C. sinensis group (n = 31). To adjust for differences in preoperative characteristics an inverse probability of treatment weighting (IPTW) analysis was done, using propensity scores. Overall survival (OS) and recurrence-free survival (RFS) were compared before and after IPTW. Multivariate Cox regression analysis was performed to determine whether the C. sinensis infection was an independent prognostic factor after IPTW. Results In original cohort, the no C. sinensis group did not show a survival advantage over the C. sinensis group. After IPTW adjustment, the median OS for the C. sinensis group was 9 months, compared to 29 months for the no C. sinensis group. C. sinensis group have worse OS than no C. sinensis group (p = 0.024), while it did not differ in RFS(p = 0.065). The multivariate Cox regression analysis showed that C. sinensis infection and lower age were associated with worse OS. Conclusions The C. sinensis infection has an adverse impact on os in srHCC patients who underwent hepatectomy.